Pengaruh Penerapan Sistem Informasi Akademik Terhadap Kualitas Layanan Administrasi Kampus - Fauziah Rahman; Pemi Budi Arti; Hari Yeni (Jurnal Ilmu Manajemen dan Akuntansi Nusantara, 2026)
The development of information technology has encouraged higher education institutions to undertake transformations in the management of academic administrative services. One form of this transformation is the implementation of an Academic Information System (SIAKAD), which aims to simplify administrative processes and improve the quality of services provided to students. This study aims to examine the extent to which the implementation of an Academic Information System influences the quality of campus administrative services. This research employs a quantitative approach, with data collected through questionnaires distributed to students as users of academic services. The collected data were analyzed using statistical analysis techniques to examine the effect of the implementation of the Academic Information System on the quality of administrative services. The results indicate that the implementation of the Academic Information System has a significant influence on the quality of campus administrative services. Improvements in service quality are reflected in the ease of system use, clarity of academic information, and efficiency of service time. The study concludes that a well-managed Academic Information System can serve as a key supporting factor in enhancing the quality of administrative services in higher education institutions.